studying of the concentrations of nutrients and chlorophyll a in summer in the sewage estuaries (outfalls) of the coastal waters in Lattakia city. (Latakia University Journal -Biological Sciences Series, 2024)
This study dealt with determination of nutrient concentrations and their spatial changes in Lattakia city, with identifying the most important hydrological parameters of water (temperature, salinity) affecting the distribution of these nutrients. A summer cruise was carried out in June 2022 in the Southern Cornich area, and determine the two largest sewage sites in it. The highest concentrations of nitrate and ammonium were recorded in the two studied sites, reaching 3.125  and  3.22 μmol/L, respectively, associated with temperature of 30.2 degrees Celsius, and salinity of 38.8‰. No clear differences were recorded in the concentrations of chlorophyll a, as the recorded concentrations ranged between0.200  and 0.412 mg/m³.